Degradation of phytate in rice bran by local bacteria phytase - Mohd Yusoff, Noraini; Mohd. Salleh, Hamzah; Jamal, Parveen (Research Journal of Chemistry and Environment, 2010)
Phytate (myo-inositol hexakisphosphates), a phosphorylated derivative of myo-inositol, is widely distributed in plants, particularly in cereals and legumes, such as corn, soybean, wheat bran, rice bran, cotton seeds, rape seeds and soybean with a concentration range between 0.4% to 6.4%. Rice bran, a by-product of rice milling, is usually either discarded as a waste or used to feed poultry and livestock. In the present work, phytase was used to hydrolyze phytate to yield inorganic orthophosphate (Pi) and a series of lower phosphoric esters of myo-inositol and in some cases, free myo-inositol. Myo-inositol phosphate intermediates formed by the dephosphorylation of phytate (IP6) by wild type phytate-degrading enzymes were partially purified by a stepwise gradient on an anion exchanger. Two different phytate degrading enzymes, ASUIA 271 and ASUIA 30 were used to degrade the myo-inositol hexakisphosphate under optimized process conditions. Phosphate released from the myo-inositol phosphates and percentage yield of the myo-inositol phosphate produced were measured and recorded. ASUIA 30 gave higher yield of myo-inositol phosphates compared to ASUIA 271.